Moisture dependent bending properties of poplar - Uğur Özkan; Tuğba Yılmaz Aydın (Turkish Journal of Forestry)
The influence of moisture on the physical (density) and mechanical (modulus of rupture-MOR, modulus of elasticity-MOE) properties of Populus x canadensis M. were figured out by three three-point bending tests and ultrasonic testing . Samples were conditioned at 20±1 °C and 45, 65, and 85% relative humidity. The calculated ultrasonic longitudinal wave velocity (VLL) was used to determine dynamic MOE (4549 to 4735 MPa) and compared to static MOE (5461 to 5910 MPa). Static MOE values are around 15.3% to 28.1% higher than dynamic values. MOR values, the most influenced properties, decreased from 70.1 MPa to 51.3 MPa with the increase in moisture. Pearson correlation coefficients ranged from 0.52 (MOR vs VLL) to 0.94 MOEdyn vs VLL). The R² values ranged from 0.187 (VLL vs MOR at 85% RH) to 0.94% (VLL vs Edyn at 65% RH).